Assessment of Poisoning Incidences due to Use of Household Substances in Peshawar - Muhammad Yousaf; Rizwan Zafar Ansari; Aftab Alam Tanoli; Inayat Ur Rehman; Riaz Gul (Gandhara University, 2018)
OBJECTIVE: The aim of this study is to determine the trend of poisoning due to household substances in Peshawar. METHODOLOGY: This was a retrospective observational study. All the information related to poisoning including mode of transmission, duration of poisoning, demographic information, duration of hospital stay, name of poison, amount of poison ingested, inhaled and intension of poisoning was from the medical record room of Khyber Teaching Hospital (KTH) casualty department. The cases reported with a history of household poisoning were recorded for a period of one year from February 2016 to January 2017. RESULTS: Among the total 217 patients, males female ratio was 1.3:1 where male 114 (51%) whereas 104 (49%) females, whereas intensity to commit suicide is more in females. Tablet overdose cases were 73 (34%) and poisoning due to common household poisons such as mosquito repellant, rat killer poison, kerosene oil, detol and detergents were 87 (36%). Victims inhaled and ingested Organophosphorous accidently and intentionally were 62 (28%). Suicidal tendency was determined to be a hallmark among females. The age group between 18 to 31 year were found highly motivated to harm themselves. It was showed 196 (91%) patients consume with intention of suicide and only 20 (9%)were found accidental victims of poisoning. CONCLUSION: It was concluded that easy accesses to anti psychotic drugs without registered doctor's prescription, self medication, over dosage and rat killing pills were found the most prevalent cause of poisoning among victims belonging to low socioeconomic status. It was also indicated in the study that most of the accidental incidents happed at home when victim was either alone or left unattended.